Effect of Soil Ameliorations on Cucumber (Cucumis sativus L) Yield and Soil Physico-chemical Properties in an Ultisol of Southeastern Nigeria - Ikeh, Angus Onwudiwe; Sampson, Helen Udoma; Ukabiala, Maduabuchi Ekeoma; Anonaba, Nkechinyere Kate; Okamigbo, Juliana Nkiru; Akuwueze, Chiamaka Gloria (Open Science and Technology, 2025)
Methods and Aims: Field experiment was conducted at Ndikpa, Umuowa Ibu 1 via National Horticultural Research Institute (NIHORT), Okigwe Sub-Station Imo state, Nigeria in 2021 and 2022 to assess the effects of different soil amelioration on performances of cucumber and soil physico-chemical properties. The treatments were organic fertilizers (goat manure, cow dung, and wood ash) and recommended dose of inorganic fertilizer (250 kg/ha NPK), and control (no soil amendment). The experiment was laid out in a randomized complete block design and replicated thrice. Soil, growth, and yield data were collected and subjected to analysis of variance. Significant means were compared with the least significant difference at 5% probability level. Result: Results showed that cow dung had the highest organic matter content after harvesting, 2.55 and 2.43 % in 2021 and 2022, while the least organic matter content of 0.71% and 0.65 % was recorded in the control. Wood ash had significantly higher K levels after harvesting, while cow dung had the highest Ca. Goat manure had significantly higher Mg and Na than the other soil amendments. Treatment of NPK had significant fruit yield of 21.12 and 22.54 t/ha in both cropping seasons, respectively. The fruit yield recorded in goat manure was 20.23 and 20.81 t/ha in both cropping seasons, while 19.80 and 17.99 t/ha fruit yield were recorded in the wood ash treatment. The fruit yield obtained from NPK treatment was not significantly different when compared with yields obtained from goat manure and cow dung treatments. The least fruit yield, 5.12 and 6.03 t/ha in 2021 and 2022 was recorded in the control treatment. Conclusion: Based on the study findings, the application of organic soil ameliorations (cow dung and goat manure) was recommended for higher fruit yields and sound soil conservation practices for sustainable crop production in an ultisol.